Is This Me? Trauma as the Breakout Point of the 'Unconscious Autobiography' of the Subject Out of the social-Cultural-Historical Matrix. - Triest, Joseph (Psychoanalytic Inquiry, 2026)
The article returns to the fundamental questions of the nature of trauma and its treatment in light of the shock caused by the massacre of October 7 – and following work with victims and with a group of therapists for the released hostages. It examines trauma as a phenomenon of the collapse of boundaries– those that distinguish between the individual (the subject embodied in the body) and the society/culture to which they belong (the subject embodied in society); between fantasy and reality; between the past and future frozen in a continuous eternal present; between the 'bad object' and 'good object'. Its main focus is an attempt to understand trauma as a breakout point (like a catastrophic volcanic eruption) of what I have termed 'the unconscious autobiography of the subject' from its social-cultural-historical context. Introspective testimony and clinical vignettes from work with victims, alongside supervisory work with a group of therapists for the hostages released from Hamas captivity, illustrate the article.